Penerapan Model Brain Based Learning Dalam Pembelajaran Pendidikan Agama Islam - Al Ayyubi, Ibnu Imam; Islamiah, Dini; Fitriyah, Dzul; Agustin, Melinda Astrianti; Rahma, Aulia (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to increase understanding and acceptance of concepts in Islamic religious learning, create a learning environment that motivates students, and optimize students' cognitive function in learning Islamic religious education. This research method uses a survey method and One Way ANOVA test analysis to see the relationship between student learning outcomes in Islamic religious education learning through the Brain-Based Learning (BBL) model and the student's school origin. The population of this study was class VIII students at MTs Arrukhshatul 'Ulum, SMP Nurul Huda Syafiiyyah, and SMP Roudlotul Ulum with a sample of 30 students at MTs Arrukhshatul 'Ulum, 29 students at SMP Nurul Huda Syafiiyyah, and 31 students at SMP Roudlotul Ulum for a total of 90 students. In this study, the average scores for student learning outcomes at Arrukhshatul 'Ulum MTs, Nurul Huda Syafiiyyah Middle School, and Roudlotul Ulum Middle School were 63.47, 64.28, 64.77. Meanwhile, the values ​​of the standard deviation are 14,044, 17,169, and 14,585. Based on the ANOVA one way test, there were no differences in student learning outcomes in learning Islamic religious education through the Brain-Based Learning model between students at MTs Arrukhshatul 'Ulum, SMP Nurul Huda Syafiiyyah, and SMP Roudlotul Ulum. So that further research can be carried out using the ANOVA two way test which can classify according to gender and cognitive level of students to find out the inherent conclusions based on inferential statistics.